Efektivitas Media PhET Simulation Terhadap Kemampuan Numerasi Siswa Kelas 5 SDN Jatingaleh 01 Pada Mata Pelajaran Matematika - Hidayah, Ulul; Utami, Rizky Esti; Wibowo, Yohanes Maria Vianey Trisunu Harjati; Ulumuddin, Arisul (LPPM Institut Pendidikan Nusantara Global, 2024)
This research aims to see the effectiveness of the PhET Simulation media on the numeracy abilities of grade 5 students at SDN Jatingaleh 01 in mathematics subjects. The method used in research is experimentation. The research design used was Pre-Experimental Design with a One-Group Pretest-Posttest Design model. The population in this study was class 5A as many as 27 students. The data collection methods used were tests and observations. From the results of the data analysis, it can be concluded that students' numeracy skills in fractional operations material using Phet Simulation media obtained a higher post-test average score of 81 compared to the pre-test average score of 51 and the results of the Ngain test showed that the average score The average Ngain of respondents was 65.2734%. This shows that the Ngain value is categorized as quite effective (range between 56%-75%). Therefore, PhET Simulation media is quite effective media to use in students' numeracy skills.